Implementasi Pengembangan Karier Guru Pendidikan Agama Islam pada Pembelajaran Digital - Islamiyah, Warda; R, Rosdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The use of career development for Islamic Religious Education (IRE) instructors in the digital learning era is the main topic of this essay. This study aims to describe and analyze the implementation of Islamic Religious Education (PAI) teachers’ career development in the context of digital learning. Adopting a liberal research approach, this study emphasizes the active engagement of teachers as change agents who are responsible for their professional careers, without over-reliance on institutional systems. Through a descriptive qualitative research design, data were collected from interviews, digital classroom observations, and learning document analysis. This study examines the difficulties instructors face when practicing online learning, including unequal access to technology and differences in teachers’ digital fluency. To understand how teachers’ career development can improve the quality of learning and assist instructors in adapting to changes in educational technology, the study used a literature review method with a deductive-inductive analysis approach. The results suggest that teachers’ technology skills can be improved through online training, yet the current digital divide needs special attention. Therefore, in addition to addressing technical issues, teachers’ career development should include more accessible and inclusive training programs. To guarantee that the quality of education is maintained in the face of changing circumstances, this study suggests the importance of policies that encourage greater access to technology and the creation of sustainable training programs.